Pengembangan Sumber Daya Manusia dalam Meningkatkan Kinerja Anggota Badan Permusyawaratan Desa di Desa Mananti Sosa Jae - Mora Rizki Hasibuan; R. Hamdani Harahap; Humaizi Humaizi (PERSPEKTIF, 2022)
This study aims to identify and analyze human resource development efforts in improving performance, obstacles and improving the performance of BPD members in Mananti Sosa Jae Village. This study uses a qualitative research method with a descriptive approach, and uses primary data collection techniques (observations, interviews) and secondary data (documentation studies). The results of this study are the development of human resources in improving the performance of members of the BPD Desa Mananti Sosa Jae carried out through planned activities, namely carrying out technical guidance activities. The obstacles to development come from the members of the BPD themselves, this is because each member of the BPD has activities outside of their work as members of the BPD, their free time is very limited in carrying out various development activities. The improvement in the performance of the members of the institution is still very low, the weakness can be seen in their ability and timeliness in completing tasks. The conclusion of this research is that although development efforts have been made, the performance improvement of BPD members is still very weak, this is caused by various obstacles in the implementation of development. human Resources.